Technology Acceptance of RemNote for Vocabulary Learning in an ESP Classroom: A TAM-Based Study - Yuni Hariyanti; Junita Duwi Purwandari; Endang Setyaningsih (English Language Education, Universitas Internasional Batam, 2026)
Vocabulary mastery is essential in second language acquisition because it supports effective communication and enhances students’ performance in reading, writing, listening, and speaking. However, vocabulary instruction in Indonesian classrooms often relies on teacher-centered approaches that may limit student engagement and autonomy. This study explores the use of RemNote, a digital note-taking and flashcard platform, to support vocabulary learning in an English for Specific Purposes (ESP) course for Sharia Economics students. Guided by the Technology Acceptance Model (TAM), the study employed a descriptive research design involving pre- and post-treatment surveys and usage data collected from 78 first-semester university students during a four-week intervention. Findings indicate positive perceptions across TAM constructs, suggesting that students viewed RemNote as useful, easy to use, and beneficial for vocabulary learning. The flashcard feature was valued for reviewing and organizing vocabulary. The study highlights RemNote’s potential as a technology-enhanced tool for vocabulary learning in ESP contexts.